Going Beyond Research on Goal Setting: A Proposed Role for Organizational Psychological Capital of Family Firms. (30th September 2013) - Memili, Esra; Welsh, Dianne H. B.; Luthans, Fred
Abstract : Kotlar and De Massis found that membership assortment and the number of organizational members, as well as the imminence of succession, influence goal diversity in family firms. They also showed that goal diversity can be managed and family‐centered goals can be stabilized through professional and familial social interactions, driving the formation of collective commitment to family‐centered goals (CCFG). Using this research as a point of departure, we propose that CCFG may impact family firm economic and noneconomic performance. Furthermore, we introduce to the family firm literature the organizational psychological capital (OPC), consisting of hope, efficacy, resilience, and optimism. We also suggest that OPC may be more prevalent in family firms than in nonfamily firms. Moreover, OPC of family firms may play an important role in the link between CCFG and economic as well as noneconomic performance.